2012
DOI: 10.1007/s00262-012-1231-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating lymphocytes predict response to chemotherapy in patients with advance non-small cell lung cancer

Abstract: Accumulating preclinical evidence suggests that anticancer immune responses contribute to the success of chemotherapy. The predictive significance of tumor-infiltrating lymphocytes (TILs) for response to neoadjuvant chemotherapy in non-small cell lung cancer (NSCLC) remains unknown. The aim of this study was to investigate the prognostic and predictive value of TIL subtypes in patients with advanced NSCLC treated with platinum-based chemotherapy. In total, 159 patients with stage III and IV NSCLC were retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 27 publications
3
96
2
2
Order By: Relevance
“…Several groups demonstrated that increased CD8 + tumor-infiltrating lymphocytes and even PD-1 + tumor-infiltrating lymphocytes were a favorable prognostic factor in various types of cancers. [45][46][47][48] These studies suggested that increased PD-1 + tumor-infiltrating lymphocytes may reflect a subset of immune cells previously activated by the antitumor immune response, and thereby correlated with a favorable clinical outcome. 48 However, PD-1 + T cells have been regarded as functionally exhausted rather than activated because of chronic and persistent antigenic exposure from either viral infection or the tumor microenvironment, suggesting that the PD-1 + /CD8 + tumor-infiltrating lymphocyte ratio might reflect attenuated cytotoxicity of CD8 + T cells against tumors.…”
Section: Discussionmentioning
confidence: 95%
“…Several groups demonstrated that increased CD8 + tumor-infiltrating lymphocytes and even PD-1 + tumor-infiltrating lymphocytes were a favorable prognostic factor in various types of cancers. [45][46][47][48] These studies suggested that increased PD-1 + tumor-infiltrating lymphocytes may reflect a subset of immune cells previously activated by the antitumor immune response, and thereby correlated with a favorable clinical outcome. 48 However, PD-1 + T cells have been regarded as functionally exhausted rather than activated because of chronic and persistent antigenic exposure from either viral infection or the tumor microenvironment, suggesting that the PD-1 + /CD8 + tumor-infiltrating lymphocyte ratio might reflect attenuated cytotoxicity of CD8 + T cells against tumors.…”
Section: Discussionmentioning
confidence: 95%
“…those with high-TILs, have a better prognosis than those with a weaker reaction. Furthermore, the density of TILs has been reported to correlate with the efficacy of chemotherapy and radiotherapy (9,10,24). Although some problems remain, such as the unification of methods for the evaluation and elucidation of the functions for each subset, TILs are now receiving a great deal of attention as potential new biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-infiltrating lymphocytes (TILs), which reflect the immune status of the host (7), have been reported to correlate with the clinical outcome, including the chemotherapeutic outcome in patients with various types of cancer (8)(9)(10). However, the method of measuring TILs has differed among previous reports (11)(12)(13)(14)(15).…”
Section: The Measurement Of Tils In the Primary Tumor Using The Methomentioning
confidence: 99%
“…Although it is unclear whether or not immune cell infiltration in small biopsies reflected those in surgically resected specimens, tumor-infiltrating lymphocytes from small biopsy specimens have been shown to predict therapy responses in advanced NSCLC. 38 Another limitation of this study was that these findings were not confirmed in a validation cohort. More importantly, although immune cell infiltrates were quantitatively similar, we did not evaluate functionality of infiltrating immune cells, as this can only be evaluated prospectively from fresh tissue.…”
Section: E967142-4 Volume 3 Issue 11 Oncoimmunologymentioning
confidence: 80%